Formulation and Characterization of An Antifungal Cream from Lawsonia Inermis Leaves Extract - Saif, Mohammad; Vyas, Girish Kumar; Ancheria, Rahul; Nama, Nitin (Journal of Neonatal Surgery, 2025)
This study investigates the antifungal and antioxidant properties of Lawsonia inermis (henna) leaves and their potential application in topical formulations. Bioactive compounds such as alkaloids, flavonoids, and tannins were identified in the plant extract. The formulation of a herbal cream with Lawsonia inermis extract exhibited potent antifungal activity against Candida albicans and Aspergillus niger, along with significant antioxidant properties. The cream demonstrated satisfactory physicochemical characteristics, including stability, spreadability, and homogeneity, and showed no skin irritation upon application. Stability studies confirmed its durability under various storage conditions. The results highlight Lawsonia inermis as a promising natural alternative for treating fungal skin infections and suggest its potential for safe and effective use in topical therapies.